Anesthetic management for emergency caesarean section and craniotomy together: an overview of the challenge - Pathak, Nidhi; Katyal, Misha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Traumatic brain injury in a pregnant woman is a challenge for anaesthesiologist, surgeon as well as paediatrician as it involves care and management of two lives together. We hereby discuss anaesthetic management of a 23 year old pregnant woman with extra axial bleed and brain contusion and skull fracture. Since the fetus was viable without signs of fetal distress, decision of doing caesarean section followed by craniotomy was taken and our patient was discharged a week later and the baby was handed over to attendant the next day.